Factors associated with chronic child malnutrition in Peru - Roldán Arbieto, Luis Humberto (2022)
Objective: To investigate factors associated with chronic malnutrition among children aged five and under in Peru. Materials and Methods: Secondary data analysis based on the Peruvian 2018 Demographic and Family Health Survey. Results: Child’s age (PR = 1.01; 95% CI: 1.009 to 1.015) and living in a rural area (PR = 1.36; 95% CI: 1.21 to 1.54) were associated with a higher risk of chronic malnutrition in the sample. Educational level, wealth index, and not belonging to the publicly funded Comedor Popular nutrition program, were identified as protective factors to chronic malnutrition. Conclusion: Being under five and living in a rural area was associated with an increased risk of chronic malnutrition in children residing in Peru. A higher wealth index and mother’s level of education decrease the chances of chronic alnutrition in children under five years of age.